2021
DOI: 10.7554/elife.69207
|View full text |Cite
|
Sign up to set email alerts
|

Protective mitochondrial fission induced by stress-responsive protein GJA1-20k

Abstract: The Connexin43 gap junction gene GJA1 has one coding exon, but its mRNA undergoes internal translation to generate N-terminal truncated isoforms of Connexin43 with the predominant isoform being only 20 kDa in size (GJA1-20k). Endogenous GJA1-20k protein is not membrane bound and has been found to increase in response to ischemic stress, localize to mitochondria, and mimic ischemic preconditioning protection in the heart. However, it is not known how GJA1-20k benefits mitochondria to provide this protection. He… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 66 publications
2
41
0
Order By: Relevance
“…Canonical mitochondrial fission is associated with DRP1 and the degradation (breakdown) of dysfunctional and damaged mitochondria ( Jheng et al, 2012 ; Friedman and Nunnari, 2014 ). In contrast, we have found that GJA1-20k induces a protective form of mitochondrial fission ( Shimura et al, 2021a ). Interestingly, GJA1-20k also stabilizes actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Canonical mitochondrial fission is associated with DRP1 and the degradation (breakdown) of dysfunctional and damaged mitochondria ( Jheng et al, 2012 ; Friedman and Nunnari, 2014 ). In contrast, we have found that GJA1-20k induces a protective form of mitochondrial fission ( Shimura et al, 2021a ). Interestingly, GJA1-20k also stabilizes actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 69%
“…Endogenous GJA1-20k expression has been reported in not just cardiomyocytes, but also in various cell types such as C33A, NF-1, MEF, A549, HEK293 ( Salat-Canela et al, 2014 ; Basheer et al, 2018 ; Shimura et al, 2021a ). In all these cell types, GJA1-20k expression is the most abundant among the N-terminus truncated small isoforms of Cx43.…”
Section: Full-length Cx43 Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…Cx43-20k also regulates the transport of mitochondria to mediate cellular response to oxidative stress, preserving mitochondrial localization and function [ 153 ]. Under cellular stress, Cx43-20k facilitates polymerization of actin around mitochondria to form focal constriction sites to initiate mitochondrial fission [ 154 ].…”
Section: Alternative Translation Of Connexin43 Mrnamentioning
confidence: 99%
“…Cx43-20K possesses a transmembrane domain and functions in cytosol [ 150 , 151 , 152 , 153 , 154 ]. Smaller fragments without any transmembrane domain, collectively called Cx43 C-terminal fragments (Cx43-CT), have been suspected to exist, and some of them have a unique nuclear localization [ 155 , 156 ].…”
Section: Cx43 C-terminal Fragment Generated By Proteomic Cleavagementioning
confidence: 99%